2015
DOI: 10.4103/0972-5229.156476
|View full text |Cite
|
Sign up to set email alerts
|

Complications during the management of pediatric refractory status epilepticus with benzodiazepine and pentobarbital infusions

Abstract: The objective of this retrospective study was to evaluate complications in the management of refractory status epilepticus (RSE) treated with benzodiazepine and pentobarbital infusions. Of 28 children with RSE, eleven (39%) were treated with a pentobarbital infusion after failure to control RSE with a benzodiazepine infusion; while17 children (61%) required only a benzodiazepine infusion. The mean maximum pentobarbital infusion dosage was 5.2 ± 1.8 mg/kg/h. Twenty-five patients received a continuous midazolam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…However, in a retrospective study, in children with acute encephalitis who presented with refractory SE, the PICU length of stay was longer and these patients had a poor neurological outcome [29]. Also, in children with refractory SE, requiring pentobarbital infusion had a longer length of hospital stay [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a retrospective study, in children with acute encephalitis who presented with refractory SE, the PICU length of stay was longer and these patients had a poor neurological outcome [29]. Also, in children with refractory SE, requiring pentobarbital infusion had a longer length of hospital stay [30].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Barberio et al reported that anaesthetic therapy using pentobarbital without bolus administration for paediatric RSE required a mean of 22.6 ± 17.5 h (0.5 to 84 h) to reach the BSP [12]. The fact that we used bolus administration is the main reason why we could reach the BSP quickly in paediatric RSE in this study; bolus administration was not used in the previous reports of barbiturate anaesthetic therapy for paediatric RSE [12][13][14]16]. Another reason is that thiamylal is an ultra-short-acting barbiturate, has high potency, and may have a less pronounced effect on the circulation than thiopental [18,21].…”
Section: Discussionmentioning
confidence: 55%
“…There are no specific recommendations regarding drug choice for coma therapy; therefore, midazolam, barbiturates, or propofol are selected based on patient condition and physician decision [1,10]. Pentobarbital or thiopental was used in most previous reports on barbiturate general anaesthetic therapy for paediatric RSE [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they were more likely to develop hypertension and movement disorder after or during weaning. [ 1 ] I presume that these results ought to be cautiously taken owing to the presence of the following three limitations. (1) The data were taken from a single center.…”
mentioning
confidence: 99%
“…Despite the aforementioned three limitations, the observation in Patten et al 's. study[ 1 ] on more complications associated with pentobarbital infusion compared to benzodiazepine infusion renders pentobarbital less recommended first-line in treating patients with RSE. This observation supports the recently published Indian consensus guidelines on the management of childhood convulsive status epilepticus[ 2 ] and recommendations of the Italian League Against Epilepsy,[ 3 ] which stress that the initial management of RSE should consist of a parenteral benzodiazepine (lorazepam, diazepam, or midazolam) by any route feasible and when first-line anti-epileptic drugs fail, sodium phenytoin, and phenobarbital should be used.…”
mentioning
confidence: 99%